Addressing the rise of autochthonous vector-borne diseases in a warming Europe - Fleischmann, Wim A.; Cao, Le Chi; Nurjadi, Dennis; Velavan, Thirumalaisamy P. (International journal of infectious diseases, 2024)
The perspective explores the emergence of autochthonous tropical diseases in Europe, driven by climate change and the associated increase in vector-borne diseases. Rising temperatures, along with changes in humidity and rainfall patterns, have altered the activity, distribution, and diversity of vectors such as mosquitoes and ticks. Species like Aedes albopictus and Aedes aegypti, which are primary vectors of dengue, have established self-sustaining populations across Europe. This spread has led to a surge in cases of dengue fever, West Nile virus, and tick-borne encephalitis in temperate regions. The complexity of predicting these outbreaks is compounded by factors like vector diapause, serological cross-reactivity, and land-use changes. The perspective calls for the implementation of enhanced surveillance, weather-linked predictive models, and robust vector control strategies to mitigate the public health risks posed by the spread of these diseases. As climate change accelerates, Europe faces increasing health threats previously confined to tropical regions, emphasizing the need for proactive public health measures to protect populations from this growing threat.